SADC Trade Protocol and its potential impact on the South African clothing and textiles industry : a case study of Pepkor - Mbono, Nontsikelelo Rose (School of Economics, 2014)
Generally, it is accepted that regional co-operation and integration is effective means to facilitate economic growth and sustainable development, particularly among the developing countries. Even the developed countries have adopted the regional approach since it is believed that its benefits outweigh the costs associated with it. Africa also acknowledged this, and formed various regional trading arrangements. However, this research focuses more on regional cooperation and integration in the SADC region. The SADC Trade Protocol was signed by all member states in 1996, with the aim to eventually form a free trade area by 2008 by gradually removing all tariffs and non-tariff barriers to intraregional trade. SADC member states are mainly concerned about the implications of the protocol on their economies, particularly the performance of their industries, as well as on trade patterns in the region. Hence, the process of ratification and implementation of the protocol has taken much longer than expected, due to ongoing negotiations between member states in an endeavour to address their concerns. Some of their major concerns are being addressed through revisions and additions to the provisions of the trade protocol. The implementation started on 01 September 2000. This research aims to establish the potential impact of the trade protocol and the proposed free trade area on the South African manufacturing industry, particularly on the clothing and textiles industry. The most crucial part of this paper is a case study, which has been conducted on one of South Africa's largest clothing companies using telephonic and face-to-face interviews, in an attempt to gain insight on the impact of the trade protocol, especially the clause on rules of origin, on the clothing and textiles industry and how the industry will continue to respond to the implementation of the protocol. How will the trade protocol impact on the trade and investment flows in the region? Will there be any specific implications on pattern of capital flows within the region? What about choice of location for future investment in the region? While there are benefits of the trade protocol for the region, through its promotion of investment and intra-regional trade and opening a larger market for the member states, it remains a concern that some member states will not benefit as much as their counterparts. The impact of the rapidly changing trade and investment environment on various sectors may differ, and the sensitive sectors remain a major concern. What are the major concerns about the clothing and textiles industry, in view of its sensitive nature? This research seeks to provide answers to various questions pertaining to the SADC trade protocol and its impact on manufacturing industry in South Africa and in the SADC region. It draws conclusions about the clothing and textiles industry as well as the manufacturing industry at large, based on the experience of one large clothing company.